Analyzing the Role of Influencers in Digital Marketing Strategy: A Case Study in the Online Fashion Industry - Andika, Albertus Deo Putra; Lestari, Esti Indah Puji; Wiliam, Afrizal (Yayasan Ilomata, 2024)
In the contemporary landscape of digital marketing, the role of influencers has become increasingly prominent, particularly within the online fashion industry. Understanding the impact of influencer collaborations on digital marketing strategy is essential for brands seeking to effectively engage with consumers in the digital sphere. This research is important because it provides a deep understanding of the role of influencers in digital marketing strategies within the online fashion industry, which is currently one of the most dynamic and competitive industries digitally. By analyzing factors such as influencer authenticity and credibility, the impact of engaging content, and strategies to enhance brand visibility and consumer engagement through influencer collaborations, this research offers invaluable insights for brands and marketing practitioners in optimizing their strategies. This study aims to analyze the role of influencers in digital marketing strategy within the online fashion industry, with a focus on their effectiveness in enhancing brand visibility and driving consumer engagement. The research explores the influence of authenticity and credibility of influencers, the impact of engaging content creation, and the strategies for building brand visibility and consumer engagement through influencer collaborations. The research methodology employed in this study involves a comprehensive review of existing literature on influencer marketing in the context of the online fashion industry. The analysis utilizes NVivo as a tool for data analysis, allowing for the systematic categorization and interpretation of key themes and findings from the literature. The analysis reveals that influencers play a significant role in shaping brand perception, driving consumer behavior, and amplifying brand reach within the online fashion industry. Authenticity and credibility emerge as crucial factors influencing consumer trust and brand loyalty. Engaging content creation by influencers proves instrumental in fostering meaningful interactions and driving consumer engagement. Strategic collaborations with influencers aligned with brand values and audience demographics are identified as effective approaches for building brand visibility and fostering consumer engagement in the digital landscape. The real implications of this research include the ability to steer more effective digital marketing practices, enhance interactions with consumers, and ultimately, improve business performance such as increased sales and the development of a loyal customer base.